Subclinical Bovine Coccidiosis in Al -Baha Area, Saudi Arabia - Mohamed Moussa Ibrahim; Maha F Soliman; Ali Othman Alghamdi (International Journal of Veterinary Science and Research - Peertechz Publications, 2015)
Subclinical bovine coccidiosis is an economic problem worldwide because they appear normal outwardly, but developmental stages damage the absorptive surface of the intestine and weaken the immune system. Information on the occurrence, diversity and economic losses due to Eimeria infection in cattle is lacking in Al-Baha area. The objective of this work was to study prevalence of subclinical bovine coccidia, throughout Al-Baha area and to evaluate various factors that might potentially influence prevalence and rate of pathogen excretion. A cross sectional study was conducted from July 2014 up to Jun 2015. Out of the total 534 fecal samples examined for Eimeria, 167 (31.27%) were found infected with eight species of Eimeria. Eimeria bovis was found to be the highest frequent species (25.84%), followed in order by E. zuernii (20.78%), E. ellipsoidalis (13.11%), E. canadensis (10.86%),E. alabamensis (8.05%), E. auburnensis (7.78%), E. cylindrica (5.43%), and E. subspherica (2.06%).Young cattle (≤12 month old) had significantly higher infection (P<0.01) of Eimeria. Higher infection of Eimeria was observed in female cattle compared to male ones. Co-infection was commonly present and declined with host age. Positive pair-wise associations were found between Eimeria species. In conclusion, this study was confirm that farm management frequently does not meet the requirements of effective coccidian control and the pathogenic coccidian, E. bovis and E. zuernii are the highest prevalent species in Al-Baha cattle populations. Further epidemiological investigations are required to investigate the different agro-ecological risk factor on the occurrence of bovine coccidiosis